A Contemplation on the Prohibition of the Marriage of a Muslim Man to an Unbelieving Woman of No Book - ÃšÂ©Ã™Â„Ã˜Â§Ã™Â†Ã˜ÂªÃ˜Â±Ã›ÂŒ, Ã˜Â¹Ã™Â„Ã›ÂŒ Ã˜Â§ÃšÂ©Ã˜Â¨Ã˜Â± (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
According to the famous or, better said, the unanimous judicial decree (fatwa) of the Muslim jurists, the marriage of a Muslim man to an unbelieving woman who adheres to any faith other than those of the People of the Book (ahl al-kitÄb) is prohibited. Although this judicial decree is based on definite evidences such as certain verses of the Qurâan, consensus of the jurists, and a number of traditional narratives, it seems the women meant by these sources are those who believe in infidelity (kufr) and polytheism (shirk) and consider themselves as devotees to pagan and profane cults. Thus this judicial decree leaves out those many women who are not familiarized with Islam and other [Abrahamic] religions and have no animosity toward the True Religion, and as described by traditional narratives, are considered helpless (mustaá¸âaf). Therefore, at least in cases of distress and constriction, one can identify the marriage of a Muslim man to such a woman, and also the subsistence of the marriage of a newly converted Muslim man to his wife, as permissible.